Non-Newtonian Evolutoids and Pedaloids of Multiplicative Plane Curves - Xinyu Yao; Haiming Liu (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to investigate properties of non-Newtonian (multiplicative) evolutoids and pedaloids of multiplicative plane curves in multiplicative Euclidean space. First, we define the notions of multiplicative pedal curve, multiplicative evolute, multiplicative evolutoids, multiplicative pedaloids, and multiplicative contrapedal of regular multiplicative plane curves. In addition, we elucidate the connection between the multiplicative evolutoids and the multiplicative pedaloids of a regular multiplicative plane curve. Next, we extend the definitions of multiplicative evolutoids and pedaloids to encompass the multiplicative frontal curves. Finally, we present two examples to demonstrate the main results.